Strategi Tingkat Bisnis,Persaingan Pasar dan Manajemen Sumber Daya Manusia Pada Penjualan PT.Citra Nusantara Catering - Syahroni, Muhammad Pupung; Suroso, Suroso; Anggela, Flora Patricia (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2022)
Catering is service requirement for some people who have a celebration for important events that bring many people to come. Catering provides food, decoration, and service for customers who have a celebration . In Karawang it self the tradition of using catering services has become a necessity of life, to help the success and smooth running of the event. One of the caterers in Karawang city is Citra Nusantara Catering, which was founded in 2018 by Mrs. Dwi Indriyani Rezeki. Promotion has an important effect on Citra Nusantara Catering to the wider community so that it can increase sales turnover. Bussines projections function as policy making and budgeting in the business. This study aims to project how the sales result of Citra Nusantara Catering in the development of small industrial businesses in Karawang Regency. Thus, this research is the first research on the application of business projection techniques using the least square method related to Citra Nusantara Catering Sales